Interannual sea-air CO2 flux variability from an observation-driven ocean mixed-layer scheme - Rödenbeck, Christian; Bakker, Dorothée C.E.; Metzl, Nicolas; Olsen, Are; Sabine, Christopher; Cassar, Nicolas; Reum, Friedemann; Keeling, Ralph F.; Heimann, Martin (Biogeosciences, 2015)
Interannual anomalies in the sea–air carbon dioxide (CO2) exchange have been estimated from surface-ocean CO2 partial pressure measurements. Available data are sufficient to constrain these anomalies in large parts of the tropical and North Pacific and in the North Atlantic, in some areas covering the period from the mid 1980s to 2011. Global interannual variability is estimated as about 0.31 Pg C yr−1 (temporal standard deviation 1993–2008). The tropical Pacific accounts for a large fraction of this global variability, closely tied to El Niño–Southern Oscillation (ENSO). Anomalies occur more than 6 months later in the east than in the west. The estimated amplitude and ENSO response are roughly consistent with independent information from atmospheric oxygen data. This both supports the variability estimated from surface-ocean carbon data and demonstrates the potential of the atmospheric oxygen signal to constrain ocean biogeochemical processes. The ocean variability estimated from surface-ocean carbon data can be used to improve land CO2 flux estimates from atmospheric inversions. publishedVersion